Influence of temperature on larval ontogenesis of Geophagus brasiliensis (Quoy & Gaimard, 1824) (Pisces: Cichlidae) - Melo, Marcelo Duarte Ventura; Paschoalini, Alessandro Loureiro; Bazzoli, Nilo (Zygote (Cambridge), 2021)
Studies on the larval development of fish are essential for conservation and improvements in cultivation techniques. Geophagus brasiliensis popularly known as Cará has potential as a fish of interest in ornamental aquaculture. Wild adults of G. brasiliensis were kept in an aquarium for spontaneous reproduction. Newly hatched larvae were transferred to 5-litre aquaria at 22, 26 and 30°C until total yolk sac resorption. Histological slides were used for biometric analysis and monitoring of larval ontogenesis at different temperatures. Histologically, from the first to the fourth days it was possible to identify myomeres, optic vesicle, yolk syncytial layer, brain, heart and differentiation of the eye layers. From the fourth to the seventh days, it was possible to identify mandibular and gill cartilages, swim bladder, liver, prismatic epithelium with striated border in intestine and renal epithelium. All biometric measurements increased over the days, except height and length of the yolk sac, which gradually decreased until the complete resorption of the yolk sac that occurred on the fifth day at a temperature of 30°C, the sixth day at 26°C and the seventh day at 22°C. Morphological events at 30°C such as the reabsorption of the yolk sac, the appearance of cartilage in the branchial arches and differentiation of the layers of the eyes occurred faster compared with the other temperatures tested. Opening of the mouth and digestive tract occurred at a similar time on the fourth day in all temperatures.